Analisis dan Perancangan Aplikasi Penyusunan Jadwal Mengajar Sesuai Jadwal Kesediaan Mengajar Dosen Di Fakultas Teknologi Informasi (Studi Kasus : Jurusan Teknik Informatika) - Meliana Christianti J.; Robby Tan; Oscar Karnalim; Egie Imandha; Tendy Cahyadi (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Faculty of Information Technology is one of the faculties at Maranatha Christian University. Currently, scheduling is still done manually. Scheduling process takes quite a long and exhaustive, as the secretary of the department needs to ask the willingness of faculty, and compare each lecturer teaching schedule so it does not clash with other lecturers. As part of Maranatha Christian University, the Faculty of Information Technology would like to shorten its preparation time to arrange faculty teaching schedule and to adjust to the schedule provided by each lecturer. This application will be developed with Java (desktop), PHP (web) programming language, and MySQL database.Â